2014
DOI: 10.19030/iber.v13i7.8913
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance And Accuracy Level Of Financial Distress Prediction Models

Abstract: This investigation verifies the impact of corporate governance measure on the likelihood of financial distress on the Spanish Stock Exchange for the time period from 2007 to 2012. The authors applied an empirical study with panel data and conducted regression logistic models with the objective to calculate different measures of goodness of fit. The results of this study show that the prediction power of the financial distress models improves with the incorporation of some corporate governance measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Governments which have motivation of the increase in financial income and encounters financial distress increase investment. de la Cruz et al (2014) investigated the effect of corporate governance on the accuracy of models of predicting financial crisis in Spain for the financial period from 2007 to 2012. The results of the research indicated that some of the mechanisms of corporate governance improve the power of predicting models of financial distress.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Governments which have motivation of the increase in financial income and encounters financial distress increase investment. de la Cruz et al (2014) investigated the effect of corporate governance on the accuracy of models of predicting financial crisis in Spain for the financial period from 2007 to 2012. The results of the research indicated that some of the mechanisms of corporate governance improve the power of predicting models of financial distress.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Kepemilikan institusional menurut Chaganti dan Damanpour (1991) adalah kepemilikan yang dimiliki oleh bank, dana pensiun, asosiasi tabungan dan pinjaman, perusahaan asuransi, dan lembaga pengelola reksadana. Sedangkan, kepemilikan manajerial yaitu kepemilikan saham yang dimiliki oleh anggota dewan direksi dan komisaris (de la Cruz et al, 2014). Menurut Joh (2003)…”
unclassified
“…Past academic studies have shown that financial distress has gained great scholarly attention in recent years (Mangena et al , 2020; Cruz et al , 2014; Cavaco et al , 2017; Marinova et al , 2015; Farag and Mallin, 2017). The term financial distress is defined by Mumford (2003) as a situation when the corporation cannot fulfil its financial obligations.…”
Section: Introductionmentioning
confidence: 99%